INVESTIGATION OF SUBSURFACE GROUNDWATER USING THE VES METHOD AROUND DENDAM LAKE, BENGKULU CITY, INDONESIA - Maghribi, Faritz Bagda; Refrizon, Refrizon; Suhendra, Suhendra; Fadli, Darmawan Ikhlas; Halauddin; Idris, Beni Syakban; Johan, Henny; Putriani, Eli (Spektra: Jurnal Fisika dan Aplikasinya, 2023)
Concerns have been raised over the availability of water in the Dendam Lake neighborhood of Bengkulu City and the areas surrounding it. The location is characterized by a number of unsuccessful water wells. These issues are the direct and indirect results of the geological formations that are present in the region, specifically Aluvium (which consists of boulders, clasts, sand, silt, mud, and clay). A MAE X-612 EM resistivity meter was utilized in order to get a total of twenty Vertical Electric Sounding (VES) measurement points. Using the software programs Progress and Surfer, the data that was gathered was plotted on a two-log graph. The geoelectric layer and layer parameter maps that were made were prepared with the use of quantitative and qualitative interpretations. It was determined that there were between three and five geoelectric layers. It has been demonstrated that the resistivity of the subsurface shallow groundwater zone ranges from 10 to 20 Ωm at a depth of 4 to 15 meters. According to the findings of this research project, employing the VES geo-electrical exploration approach is likely capable of effectively outlining the subsurface and shallow groundwater. In addition, there is no information available regarding the precise depth of the groundwater table in the region. On the other hand, the underground groundwater at this location has a depth that is shallower than the norm.